The mysterious whispers - Haq, Roohi (Karachi : Paramount books, 2014)
"The Mysterious Whispers" likely involves a bear-like character and a dog who encounter some puzzling whispers. Set in an outdoor environment with trees and a fence, the story probably centers around them trying to uncover the source or meaning of these mysterious sounds. Their adventure could involve some element of light investigation or problem-solving.
Location: 3B
Keywords: Story book